Analisis Menyusun Anggaran Untuk Menentukan Penerimaan Dan Pengeluaran Kota Malang - Inggrid Debby Ekza Veronica; Reza Akbar Mauliza; Muhammad Yasin (Journal of Creative Student Research, 2023)
APBD is one of the tools to improve public services and welfare in the community according to the broad and real goals of regional autonomy. This study aims to find out whether the preparation of the APBD in Malang City is in accordance with Government Regulation Number 12 of 2019 concerning Regional Financial Management, Minister of Home Affairs Regulation Number 90 of 2019 and Malang Mayor Regulation Number 24 of 2020 concerning the 2021 Kola Malang Regional Government Work Plan. The research method used is descriptive method, each data collected is analyzed and a conclusion is drawn. The type of research used is descriptive qualitative. The research results obtained are that the process of preparing the Malang City APBD in accordance with Government Regulation Number 12 of 2019 Minister of Home Affairs Regulation Number 90 of 2019 has been carried out properly.